2002
DOI: 10.1046/j.1365-2168.2002.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of stapled haemorrhoidopexy versus conventional diathermy haemorrhoidectomy

Abstract: The stapled operation was significantly less painful than conventional haemorrhoidectomy. However, the rate of recurrent prolapse was higher after stapled haemorrhoidopexy than after conventional diathermy haemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
258
4
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(283 citation statements)
references
References 24 publications
9
258
4
12
Order By: Relevance
“…20-29-31 In a study, Ortiz et al determined tenesmus at the rate of 40% and revealed the opinion that this depends on making sac suture at a low level. 29 The stapler line close the dentate line was noted only in 1 patient with complaint of tenesmus in our cases. In others, no reason explaining the complaint was determined.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…20-29-31 In a study, Ortiz et al determined tenesmus at the rate of 40% and revealed the opinion that this depends on making sac suture at a low level. 29 The stapler line close the dentate line was noted only in 1 patient with complaint of tenesmus in our cases. In others, no reason explaining the complaint was determined.…”
Section: Discussionmentioning
confidence: 98%
“…In studies related to this, rates between 0.3% and 20% were reported. 12,29 In our series, urinary retention was seen in 2 patients (3%) in whom spinal anesthesia was applied. Drainage was achieved by means of placement of urinary catheter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the recent literature, a significant incidence of recurrence after stapled hemorrhoidopexy was reported. In studies evaluating stapl ed hem orrhoid opexy and conventional hemorrhoidectomy for Grade III and IV hemorrhoids with an adequate and systematic follow-up (>1 year), the incidence of recurrence was 0 to 26 % and 0 to 10.8 %, respectively; reoperation rate was up to 16.7 % after stapled hemorrhoidopexy [43,46,61,[63][64][65][70][71][72]. After conventional Ferguson's hemorrhoidectomy, a redo surgery for recurrent hemorrhoids was necessary in 0.8 % of cases in a large series [73].…”
Section: Resultsmentioning
confidence: 99%